Pengaruh Motivasi dan Pengawasan Terhadap Kinerja Karyawan PT. PGASCOM Palembang - Wiwin Agustian; Hendri Hendri (MBIA, 2018)
The availability of telecommunication network enables a company to be able to establish good relationships in the internal relationship between the leadership with employees or with external parties in the form of relationships with suppliers, business partners and the community. PT PGASCOM is a subsidiary of PT Gas Negara (Persero) Tbk engaged in providing telecommunication network services. As a backbone provider, PT.PGASCOM operates a fiber optic network for the telecommunications industry in Indonesia. This study aims to determine whether the partial and simultaneous motivation and supervision affect the performance of employees at PT. PGASCOM Palembang. Technical analysis used is descriptive quantitative by using tabulation, correlation coefficient, coefficient of determination and doubled linear regression analysis, The result of research indicate that there is partially and simultant influence between Motivation and Supervision to Employee Performance at PT. PGASCOM Palembang.